Abordagem em saúde pública da associação do conhecimento, condição periodontal e controle glicêmico de pacientes diabéticos tipo 2 - Valentim, Flavia Bridi (2018)
Background: Periodontitis control aids to prevent and control the diabetes mellitus (DM) and the understanding of this relationship has the potential to cause changes health policy. Aim: To verify, in diabetic patients, oral hygiene habits; referral, attendance and dental care history; self-observed mouth clinical features that may be related to periodontitis manifestation; DM glycemic control and its relationship with periodontitis; knowledge of periodontal disease (PD) and its relationship with DM. Methods: A crosssectional epidemiological study was conducted with 288 patients with type 2 DM of both sexes, nonsmokers, aged ≥18 years and with at least one tooth. A validated structured questionnaire was used to data collection. In a second moment, only the 216 patients who had recent blood tests with glycated hemoglobin (HbA1c) were selected from the total sample. Adequate DM control was considered with HbA1c ≤7%. Descriptive statistical analysis and simple and multiple logistic regressions were performed. Results: For the study population, more than 90% of the patients reported brushing their teeth twice a day or more; more than 60% reported having visited a dentist in the last year; approximately 80% have already undergone PD treatment; the medical referral rate for dental treatment was between 13 and 15%; and about half of the patients had periodontitis. Patients with higher education level, who flossing daily, with periodontitis and who received treatment for this disease were more likely to have received information on what is PD (p <0.05; OR> 2). Patients with higher education level and longer DM diagnosis had a greater chance of being told about the relationship between PD and DM (p <0.05; OR> 2). Of the 216 patients who had a blood test with HbA1c rate, 59.72% had controlled DM. No significant association was observed (p=0.603) between HbA1c control and presence of periodontitis. For the patients with periodontitis, there was also no association between HbA1c control, being told about PD (p=0.921) and know about the relationship between PD and DM (p=0.650). Conclusion: The diabetic patients of this study had adequate oral hygiene habits, frequency of care and dental treatment, but only the smallest part of the sample received medical referral to the dentist. It was observed a relationship between the knowledge of PD and its relationship with education level, oral health and dental treatment. No relationship was found between periodontitis and glycemic control of DM.